UPAYA PENGEMBANGAN SERTA PROSEDUR PERMOHONAN DESAIN INDUSTRI KERAJINAN KAYU DI BALI - Urmila Dewi Manuaba, Ida Ayu; Wiryawan, I Wayan (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014, 2014)
Industrial design in this era of globalization, especially in Bali has a very important role because it can create a product that can provide a big advantage in the field of industry and trade. Purpose of this paper is to investigate the development efforts of wooden handicrafts and industrial design application procedure in Bali wood craft. This study uses empirical type of research that the juridical conceptualize an empirical phenomenon that can be observed in real life. Conclusion of this paper is the design development efforts wood craft industry is to improve aspects of production and marketing aspects in the country or abroad as well as industrial design application for wood crafts can be submitted in writing to the Indonesian Directorate General of Intellectual Property Rights.
Keywords: Development, Petition, Industrial Design, Woodcraft